2021
DOI: 10.1016/j.cmet.2021.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyhypusine synthase promotes a pro-inflammatory macrophage phenotype

Abstract: Highlights d eIF5A Hyp is enriched in adipose tissue macrophages in obesity d Proinflammatory macrophages augment DHPS and eIF5A Hyp production d DHPS supports the production of proteins that promote NFkB signaling in macrophages d Dhps deletion in macrophages of obese mice improves insulin sensitivity and glycemia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 67 publications
1
27
1
Order By: Relevance
“…In our study, we subjected zebrafish larvae to a “two-hit” paradigm, wherein they were first fed a lipid-rich diet to excess, followed by induction of cytokines using our Liver-CETI-PIC3 system. We studied macrophage infiltration using the Tg(mpeg:GFP) line that we have well-characterized for studying migration and infiltration of these immune cells in other inflammation models [ 36 , 37 ]. Curiously, while the animals subjected to the HFD alone exhibited a clear inflammatory response, those only mis-expressing cytokines hepatically via Li-PIC3 did not.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we subjected zebrafish larvae to a “two-hit” paradigm, wherein they were first fed a lipid-rich diet to excess, followed by induction of cytokines using our Liver-CETI-PIC3 system. We studied macrophage infiltration using the Tg(mpeg:GFP) line that we have well-characterized for studying migration and infiltration of these immune cells in other inflammation models [ 36 , 37 ]. Curiously, while the animals subjected to the HFD alone exhibited a clear inflammatory response, those only mis-expressing cytokines hepatically via Li-PIC3 did not.…”
Section: Discussionmentioning
confidence: 99%
“…eIF5A is the only protein known to be posttranslationally modified via hypusination: (1) deoxyhypusine synthase (DHPS) transfers the 4-aminobutyl group derived from spermidine to the eIF5A Lys50-deoxyhypusine ; (2) deoxyhypusine hydroxylase (DOHH) catalyzes the hydroxylation to generate eIF5A hyp . Since global deletion of Dhps is embryonic lethal in mice, cell-type-specific deletions are required [16]. Puleston et al generated Dohh-∆T and Dhps-∆T mice to specifically delete DOHH and DHPS, respectively, in CD4+ T cells [13].…”
Section: Deficiency In Polyamine Biosynthesis In Cd4+ T Cells Confers...mentioning
confidence: 99%
“…Pro-inflammatory macrophage infiltration into adipose tissue is a hallmark of the metabolic inflammation of obesity that leads in fine to diabetes. Anderson-Baucum et al [ 130 ] found that the hypusinated form of eIF5A was increased in adipose tissue macrophages M1, which exhibit a proinflammatory phenotype in obese mice. They report that targeting DHPS in myeloid cells of obese mice decreased M1 macrophage infiltration and improved the sensitivity to insulin.…”
Section: Diabetes and Pancreasmentioning
confidence: 99%